Development of a steel-guide connection method for composite precast concrete components - Hong, Won-Kee; Kim, Gyeongju; Lim, Chaeyeon; Kim, Sunkuk (Journal of Civil Engineering and Management, 2017)
Green Frame is a column-beam structure formed by connecting a composite precast concrete beam with a steel connection on the column side. Similar to steel frame construction, the green columns cover 3 stories per unit, and generate vertical and horizontal eccentricities due to construction errors and the gravitational loads of beams. Such eccentricities make it difficult to install the upper floor beams and adjacent frames. This problem not only results in decreased productivity, but also in time delays and cost overrun. The objective of this study is to develop a new steel-guide connection method for composite precast concrete (CPC) components after analysing the erection process and structural mechanism to resolve eccentricity issues. The connection mechanism developed in this study resolves these eccentricities and promotes efficient, accurate, and safe construction. First published online: 01 Jul 2016